Performance of Red Skin and Nutrient Rich Advanced Potato Clones under North-central Conditions of India - Sadawarti, Murlidhar J.; Luthra, S. K.; Kumar, Vinod; Gupta, V. K.; Singh, S. P.; Katare, Subhash; Samadhiya, R. K.; Verma, Darminder; Sharma, S. K.; Singh, Surender; et al. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted at ICAR-CPRI-RS, Gwalior (M.P.) from 2022–2023 to 2024–2025 with three red skinned advanced clones namely MS/13-527, MS/14-1381 and MS/17-848 along with eight control varieties namely Kufri Lalit, Kufri Lohit, Kufri Lalima (red skin), Kufri Neelkanth and Kufri Jamunia (purple skin nutrient-rich), and Kufri Khyati, Kufri Pukhraj, and Kufri Mohan (white or yellow skin) for growth, tuber yield, tuber and haulm dry matter parameters under the Gwalior conditions of North-Central conditions of India in 3 replications of RBD. The emergence percentage among all genotypes exceeded 85%. Kufri Lalima (74.2 cm), Kufri Neelkanth (67.2) and MS/13-527 (78.7) exhibited significantly the highest plant height, stem count, and number of compound leaves per plant, respectively. The nutrient-rich clone MS/17-848 demonstrated comparable marketable yields (31.94 and 36.52 t ha-1) and total tuber yields (34.35 and 38.86 t ha-1) at 75 and 90 days, respectively, with nutrient-superior varieties Kufri Jamunia and Kufri Neelkanth. The red-skinned advanced clone MS/14-1381 and the control cultivar Kufri Lohit achieved significantly higher marketable and total tuber yields compared to other white-skinned and coloured control varieties. The Kufri Lalima (red skin) variety (19.45% and 20.27% at 75 and 90 days), followed by the Kufri Neelkanth (nutrient-rich) variety (18.99% and 20.87% at 75 and 90 days), recorded significantly high dry matter. Therefore, the red-skinned hybrid MS/14-1381 (now released as Kufri Ratan) and the Kufri Lohit cultivar were identified as the best performers under the North-Central conditions of India.